Internalization of Islamic Law in the Formation of Regional Regulations in Lampung Province - al Arif, M. Yasin; Indra, Gandhi Liyorba; Susanto, Is (Universitas Islam Negeri Raden Intan Lampung, 2023)
The Formation of Regional Regulations in Indonesia, including in Lampung Province, is an integral part of the government's efforts to regulate community life effectively and efficiently. Islamic legal values have become an important factor influencing the formation of regional regulations (Perda). Lampung Province, one of Indonesia's regions rich in cultural and religious diversity, demonstrates significant adoption of Islamic legal aspects in various local regulations. This research is a normative legal study based on literature with a legislative approach and legal interpretation analysis. The data analysis method used is content analysis. The results show that Islamic law significantly influences the formation of regional regulations in Lampung Province. This is reflected in several regional regulations that adopt Islamic law principles in various aspects of community life. The internalization of Islamic legal values in these regional regulations is concrete evidence of the adaptation and harmonization between Islamic law and the national legal context in Indonesia. This research implies the importance of considering religious aspects in formulating regional legal policies to achieve social justice and harmony among communities with various backgrounds and beliefs.